Razões e consequências da falência de agroindústrias canavieiras em Minas Gerais - Santos, Suellen Barth dos (2021)
Sugarcane agribusiness has a relevant role in the Brazilian economy for generating jobs and foreign exchange. However, the sucroenergetic sector has been going through a crisis with decreased sugarcane production and failure. Therefore, this research aims to analyze and understand the reasons and consequences of the bankruptcy of sugarcane agribusinesses in Minas Gerais State (Brazil). For this, an explanatory methodological approach was used through primary data collection and field research. The questionnaire, answered by the directors of the plants/distilleries located in Minas Gerais, points out managers' lack of knowledge as an obstacle to decision-making in the face of adversities imposed by the market and hindering the strategic growth of the units. As for field research, even though it is an agro-industrial unit undergoing judicial recovery (located in Passos) and another bankrupt unit (located in São Sebastião do Paraíso), the causes for both situations converge to inadequate financial and administrative management. In both municipalities visited, the adverse effects of judicial reorganization and bankruptcy mainly affected the leased landowners. It shows that business preparation is a differential to face the competitiveness in the sucroenergetic sector. It should also be noted that bankruptcy situations have contributed to a greater concentration of the industry.